Minimal Impacts of Tyre Particle Exposure on Estuarine Meiofaunal Community Structure, Primary Production, and Nutrient Cycling - Charlotte Woodhouse; Dannielle Senga Green; Andy Foggo; Paul J. Somerfield; Richard C. Thompson; Samantha L. Garrard (Journal of Marine Science and Engineering)
Tyre wear particles are a significant source of primary microplastics in the natural environment with the potential to accumulate in aquatic sediments, yet our understanding of the ecological impact of these particles is limited. Using mesocosms of estuarine sediment containing a model macrofauna community (Scrobicularia plana and Hediste diversicolor), meiofauna, and microphytobenthos, we investigated the impact of exposure to sedimentary tyre particles (0.2, 1, and 5% kg sediment(dw)−1) upon meiofauna community structure, primary production, secondary production, and nutrient fluxes. Under the conditions (13 °C) and timescale (31 days) investigated, exposure to sedimentary tyre particles did not lead to any significant differences in nutrients for primary productivity, with limited impact on meiofaunal secondary productivity. An increase in Tanaidacea was observed in 1% and 5% tyre particle treatments, putatively due to reduced macrofaunal predation. Previous studies have highlighted the ecotoxicity of tyre wear particles. The limited impacts on meiofauna may be due to our experimental particles being too large for meiofauna to ingest or the timescale of the experiment being too short to witness changes at the community scale. Impacts from tyre particle leachates were likely limited due to dilution in the partial recirculation system. Leachate dilution will occur naturally in marine systems and should be a consideration in the design of future studies.